High-rate low-temperature-resistant electrolyte adaptive to high-density polyphenylene sulfide solid-state diaphragm, preparation method and lithium battery

By adding specific types of solvents and co-solvents to the lithium metal battery electrolyte, the problem of the charge and discharge performance and capacity of lithium metal batteries in low temperature environments is solved, and the rate performance and low temperature performance of the high-density polyphenylene sulfide solid separator is significantly improved.

CN119627209APending Publication Date: 2025-03-14JIANGSU UNIV

Patent Information

Application Number
CN202411679140.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The charge and discharge performance and capacity of lithium metal batteries in low temperature environments are significantly affected, and the rate performance and low temperature performance of the high-density polyphenylene sulfide solid separator are poor, hindering its commercial application.

Method used

A high-rate low-temperature resistant electrolyte suitable for high-density polyphenylene sulfide solid separators was developed. By adding acyclic carbonate solvent, cyclic carbonate solvent, linear ester co-solvent and film-forming additives to the electrolyte, the composition of the electrolyte is optimized to improve the rate performance and low-temperature performance of the battery.

Benefits of technology

The electrolyte significantly improves the capacity retention and cycle stability of lithium metal batteries under high magnification and low temperature conditions, and is better than the combined performance of commercial electrolytes and solid-state separators.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005147844620000061
    Figure BDA0005147844620000061
  • Figure HDA0005147844630000011
    Figure HDA0005147844630000011
  • Figure HDA0005147844630000012
    Figure HDA0005147844630000012
Patent Text Reader

Abstract

The invention relates to the field of new energy materials, and discloses a high-rate low-temperature-resistant electrolyte adaptive to a high-density polyphenylene sulfide solid diaphragm, a preparation method and a lithium battery, and an organic solvent of the electrolyte comprises acyclic carbonate, cyclic carbonate, a cosolvent and a film-forming additive. The cosolvent is linear ester of which the freezing point is lower than-40 DEG C; the acyclic carbonate which can generate weak dipole adsorption or repulsive interaction with the surface of high-crystallization polyphenylene sulfide is selected as the acyclic carbonate, and the solvent can form a solvation cluster with Li < + > in the electrolyte and can accelerate Li < + > desolvation on the surface of the PPS solid diaphragm, so that Li < + > smoothly passes through a sulfur channel, and the rate capability of the battery is improved; the linear ester with low freezing point makes up the defect that the freezing point of cyclic carbonate and acyclic carbonate is too high, so that the battery can normally work at-20 DEG C, and the low-temperature performance of the electrolyte is improved. By adding the film-forming additive, the safety of the battery is improved, and the cycle life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium ion batteries, and in particular to a high-rate low-temperature resistant electrolyte suitable for a high-density polyphenylene sulfide solid diaphragm and a preparation method thereof. Background Art

[0002] In recent years, with the continuous innovation of power battery technology and the vigorous development of the new energy vehicle industry chain, the penetration rate of the electric vehicle market has been significantly improved. Lithium-ion batteries (LIBs) perfectly meet the needs of most chemical power sources with their high energy density, long cycle life, suitable operating voltage and energy-saving and environmental protection characteristics, and are gradually seizing the market share of traditional lead-acid batteries, nickel-cadmium batteries and zinc-manganese batteries. Compared with lithium-ion batteries, lithium metal batteries (LMBs) have higher energy density and can provide longer driving range. This feature makes lithium metal batteries have significant advantages in application scenarios requiring high energy output. Solid-state LMBs are considered to be the most promising energy storage method. Solid-state electrolytes (SSEs) can inhibit the formation of Li dendrites, thereby fundamentally solving the safety and cycle problems of LMBs. However, the high interface impedance between the electrode and the solid electrolyte and the poor ionic conductivity are the two key problems that hinder the commercialization of lithium-ion solid-state batteries. One way to solve the above problems is to use high-density solid separator polyphenylene sulfide (PPS) with excellent electrolyte wettability and high ionic conductivity, and achieve a quasi-solid route by adding liquid electrolytes.

[0003] When LMB works in a low temperature environment, its charge and discharge performance and capacity will be significantly affected. As the temperature decreases, the charge and discharge rate and available capacity of the battery will decrease significantly due to the increase in electrolyte viscosity, the decrease in conductivity, and the significant increase in the impedance of the SEI film. This has greatly hindered the promotion of LMB worldwide, especially in areas that are in a low temperature environment all year round, where the use of LMB is hindered. Patent 202010573661.9 uses ordinary commercial electrolytes (1M LiPF6 in DEC / EC=7:3) and a dual salt electrolyte (1.2M LiBF4 / LiDFOB in DEC / FEC=2:1v / v), which can show excellent cycle performance at room temperature. However, poor rate performance and unsatisfactory low temperature performance hinder the development of PPS solid diaphragms. Therefore, it is urgent to find a high-rate and low-temperature resistant electrolyte suitable for high-density polyphenylene sulfide solid diaphragms to provide more efficient and reliable energy solutions for electric vehicles, energy storage systems and other fields. Summary of the invention

[0004] The present invention aims to solve the problem that the existing lithium metal battery using commercial electrolyte / polyphenylene sulfide solid diaphragm has poor rate and low temperature performance, and provides a high-rate low-temperature resistant electrolyte suitable for high-density polyphenylene sulfide solid diaphragm and a preparation method. Through the deployment of organic solvents and the coordination of co-solvents, it can be applied to improve the rate performance of high-density polyphenylene sulfide solid diaphragm and improve its available battery capacity under low temperature conditions.

[0005] In order to achieve the above-mentioned object, according to one aspect of the present invention, there is provided a lithium-ion battery electrolyte, characterized in that it comprises an organic solvent, a co-solvent, a lithium salt, and a film-forming additive, wherein the organic solvent comprises an acyclic carbonate solvent and a cyclic carbonate solvent, the acyclic carbonate solvent is selected from an acyclic carbonate that can produce weak dipole adsorption or repulsion with the surface of highly crystalline polyphenylene sulfide PPS, and the adsorption energy barrier of the acyclic carbonate on the PPS surface is greater than -0.33 eV; the co-solvent is a linear ester with a freezing point below -40°C.

[0006] Preferably, in the lithium-ion battery electrolyte, by mass percentage, the lithium salt is 12%-18%; the film-forming additive is 3%-5%; and the balance is the organic solvent, which is 100% in total.

[0007] Preferably, in the organic solvent, the mass percentage of the cyclic carbonate solvent is 20%-30%, the mass percentage of the acyclic carbonate solvent is 40%-60%, and the mass percentage of the co-solvent is 20%-30%;

[0008] Preferably, the cyclic carbonate solvent is selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), and vinylene carbonate (VC).

[0009] Preferably, the acyclic carbonate solvent is selected from one or more of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), ethyl trifluoroethyl carbonate (ETFEC), and methyl trifluoroethyl carbonate (FEMC).

[0010] Preferably, the co-solvent is selected from one or more of ethyl propionate (EP), methyl propionate (MP), methyl acetate (MA), ethyl propionate (EP), and ethyl acetate (EA).

[0011] Preferably, the lithium salt is lithium hexafluorophosphate (LiPF6) and / or lithium bis(fluorosulfonyl)imide (LiFSI); the concentration of the lithium salt is 1.3-2 mol / L, and the mass percentage in the electrolyte is 12%-18%.

[0012] Preferably, the mass percentage of the film-forming additive in the electrolyte is 3%-5%.

[0013] Preferably, the film-forming additive is selected from one or more of lithium tetrafluoroborate (LiBF4), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), and tris(hexafluoroisopropyl) phosphate (THFP).

[0014] The preparation method of the electrolyte is characterized in that lithium salt, acyclic carbonate, cyclic carbonate, linear ester, film-forming additive and anti-overcharge additive are weighed according to the target composition and ratio of the electrolyte, the acyclic carbonate, cyclic carbonate and linear ester are mixed evenly in a glove box filled with inert gas, and then the lithium salt, film-forming additive and anti-overcharge additive are added to the mixed solution, stirred to dissolve and mixed evenly to obtain the electrolyte.

[0015] A lithium battery, characterized in that the electrolyte of the lithium battery is the electrolyte described in any one of claims 1-9.

[0016] Beneficial effects:

[0017] In the electrolyte of the present invention, cyclic carbonates (such as EC) can effectively resist oxidation and reduction reactions and prevent decomposition and deterioration of the electrolyte. In addition, the addition of cyclic carbonates helps to form a benign solid electrolyte interface film (SEI) on the surface of the electrode. This film can protect the electrode from being corroded by the electrolyte and provide a channel for lithium ion transmission, so that the cycle stability of the battery is significantly improved. The acyclic carbonate of the present invention is selected from acyclic carbonates that can generate weak dipole adsorption or repulsion with the surface of high-crystalline polyphenylene sulfide PPS. The adsorption energy barrier of the acyclic carbonate on the surface of PPS is greater than -0.33 eV. According to experiments and theoretical calculations, ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), ethyl trifluoroethyl carbonate (ETFEC), methyl trifluoroethyl carbonate (FEMC) and the like are not compatible with the surface of PPS. Under low temperature conditions and high magnification, this type of acyclic carbonate can form solvated clusters with lithium ions. The clusters are easily desolvated and decoupled on the surface of PPS, so that the solvent molecules are not easy to block the transmission channels of the dense PPS diaphragm, so that Li +It can smoothly enter the sulfur site channels on the surface of PPS at low temperatures and migrate to the anode, ensuring its excellent capacity retention rate. Solvents such as diethyl carbonate (DEC) are easily compatible with the surface of PPS, not easily desolvated, and easily block the transmission interface of the dense diaphragm, showing unsatisfactory rate and low-temperature performance. The addition of co-solvents makes up for the defect that the freezing point of cyclic carbonates and acyclic carbonates is too high, causing the electrolyte to solidify at low temperatures (below -20°C). The freezing points of these linear esters are almost all below -70°C. Only 20%-30% of the mass percentage of the organic solvent needs to be added to ensure the fluidity of the electrolyte at low temperatures, and it has the advantages of a moderate dielectric constant and a wide electrochemical window. At the same time, a film-forming additive with a mass percentage of 3%-5% is added to the electrolyte. The film-forming additive selected by the present invention can not only form a stable solid electrolyte interface (SEI) on the electrode surface at low temperature, this thin film can prevent the electrode from directly contacting the electrolyte and reduce the occurrence of side reactions; it can also effectively reduce the low-temperature impedance of the battery and improve the low-temperature discharge capacity and cycle stability of the battery.

[0018] The electrolyte provided by the present invention is suitable for the polyphenylene sulfide solid diaphragm, and the ion conductivity at room temperature is 10 -3 Scm -1 Above, at -20℃ to -10℃, its ionic conductivity is also 10 -4 S cm -1 In the room temperature rate test of LMB, even if the charge and discharge rate reaches 3C, the battery can still maintain a capacity retention rate of more than 80%. This solution has exceeded the capacity retention rate (74.8%) of its application in commercial PE diaphragms. In the low temperature test, even under the harsh conditions of -20℃, at a high rate of 0.5C, the capacity retention rate can still reach more than 50%. After the conductivity test, at room temperature, the electrolyte and the PPS solid diaphragm cooperate with each other to reach 10 -3 S cm -1 In the low temperature test, even below -20℃, the ionic conductivity can still reach 10 -4 S cm -1 This is almost twice the conductivity when coupled with a commercial PE separator. The electrolyte has significant advantages at high rates and low temperatures. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Capacity comparison chart of LFP / / Li button cells with PPS solid-state separators made with the DEC-based electrolyte of Example 1 and the DMC-based electrolyte of Comparative Example 1 at 25°C and 2C.

[0020] Figure 2(a) and (b) are the first cycle charge and discharge curves of the LFP / / Li button battery with a PPS solid diaphragm made of the DEC-based electrolyte in Example 1 at -10°C and -20°C, 0.1C conditions, respectively, using the LFP button battery with the electrolyte prepared in Example 1, specifically (a) is -10°C, 0.1C; (b) is -20°C, 0.1C. DETAILED DESCRIPTION

[0021] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. Preferred embodiments of the present invention are given. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein.

[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing the embodiments of the present invention and are not intended to limit the present invention.

[0023] In order to solve the problem of poor rate performance and poor low temperature performance of high-density polyphenylene sulfide solid diaphragm. The present invention prepares an electrolyte with low freezing point and high conductivity, and adds a film-forming additive thereto, further prolonging the storage life and cycle life of the battery, improving the discharge capacity of the battery at high rate and the capacity retention rate under low temperature environment, and improving the dilemma of poor electrochemical compatibility with lithium metal negative electrode materials. The electrolyte includes: lithium salt, organic solvent, co-solvent and film-forming additive, and the organic solvent needs to contain an acyclic carbonate solvent with an adsorption energy barrier greater than -0.33eV on the PPS surface. This type of solvent is not compatible with the high-crystalline PPS surface and can form solvated clusters with lithium ions. The clusters are easy to desolvate and decouple on the PPS surface, so that the solvent molecules are not easy to block the transmission channel of the dense PPS diaphragm, so that Li+ can smoothly enter the sulfur channel on the PPS surface at low temperature and migrate to the anode, ensuring its excellent capacity retention rate. The acyclic carbonate solvents available include ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), ethyl trifluoroethyl carbonate (ETFEC), methyl trifluoroethyl carbonate (FEMC) and the like.

[0024] Embodiment 1:

[0025] The adsorption energy barrier of PPS surface with DMC calculated by first principles is -0.326eV, while that with DEC is -0.376eV. Therefore, DMC meets the screening requirements of acyclic carbonates.

[0026] In a glove box filled with argon (water content <0.1ppm, oxygen content <0.1ppm), dimethyl carbonate (DMC), ethylene carbonate (EC), and methyl propionate (MP) are mixed in a mass ratio of 4:3:3 to obtain a mixed solvent, and then lithium hexafluorophosphate (LiPF6) is added, and its mass percentage in the electrolyte is 15%. Lithium tetrafluoroborate (LiBF4) and lithium difluorooxalatoborate (LiDFOB) are added, stirred, mixed and dissolved, and their mass contents in the electrolyte are 1% and 2%, respectively, and the electrolyte is obtained by mixing, which is recorded as DMC-based electrolyte.

[0027] Embodiment 2:

[0028] The difference between Example 2 and Example 1 is that the type of acyclic carbonate is different, that is, ethyl methyl carbonate (EMC) is used instead of dimethyl carbonate (DMC) in Example 1, and the lithium salt concentration and ratio, and the additive content are the same as those in Example 1.

[0029] Embodiment 3:

[0030] The difference between Example 2 and Example 1 is that the type of co-solvent is different, that is, methyl acetate (MA) is used instead of methyl propionate (MP) in Example 1, and the lithium salt concentration and ratio, and the additive content are the same as those in Example 1.

[0031] Embodiment 4:

[0032] The difference between Example 2 and Example 1 is that the ratio of the organic solvent is different, that is, dimethyl carbonate (DMC), ethylene carbonate (EC), and methyl propionate (MP) are used in a mass ratio of 5:3:2 instead of 4:3:3 in Example 1, and the lithium salt concentration and additive content are the same as in Example 1.

[0033] Comparative Example 1

[0034] The difference between Comparative Example 1 and Example 1 is that the type of acyclic carbonate is different, that is, diethyl carbonate (DEC) is used instead of dimethyl carbonate (DMC) in Example 1, and the lithium salt concentration and ratio, and the additive content are the same as those in Example 1. It is recorded as DEC-based electrolyte.

[0035] Comparative Example 2

[0036] The difference between Comparative Example 2 and Example 1 is that the auxiliary solvent methyl propionate (MP) is not contained, the mass ratio of the organic solvent is dimethyl carbonate (DMC):ethylene carbonate (EC)=7:3, and the lithium salt concentration and additive content are the same as those in Example 1.

[0037] The present invention also provides a lithium battery, which uses lithium iron phosphate (LFP) as a positive electrode active material, conductive carbon black (ECP) as a conductive agent, polytetrafluoroethylene (PTFE) as a binder, and an electrode sheet is made by a dry electrode process according to a mass ratio of 90:5:5, and the load of lithium iron phosphate (LFP) is ≈20mg / cm 2 , the negative electrode is a lithium sheet, and the button battery is made in a glove box filled with argon.

[0038] In order to verify the performance of the electrolyte of the present invention, the above-mentioned Examples 1-4 and Comparative Examples 1 and 2 were used as electrolytes, and commercial PE diaphragms and polyphenylene sulfide (PPS) solid diaphragms were used as battery diaphragms to make button batteries for electrical performance testing. The electrolytes of Example 1 and Comparative Example 1 were used to form button batteries for comparison.

[0039] Testing method and process of lithium iron phosphate positive electrode:

[0040] Normal temperature test: At 25℃, charge and discharge at constant currents of 0.1C / 0.1C, 0.2C / 0.2C, 0.5C / 0.5C, 1C / 1C, 2C / 2C, and 3C / 3C respectively to allow the battery to be rate tested within the voltage range of 2-4.2V.

[0041] Low temperature test: at -10℃ and -20℃ respectively, with constant current charge and discharge at 0.1C / 0.1C, 0.2C / 0.2C, 0.5C / 0.5C, 1C / 1C, the battery was tested within the voltage range of 2-4.2V.

[0042] Figure 1 The capacity comparison chart at 2C of the DEC-based electrolyte of Example 1 and the DMC-based electrolyte of Comparative Example 1 in the LFP / / Li button battery with a PPS solid-state separator shows that the rate performance of the DMC-based electrolyte is better, and the 2C capacity retention rate reaches 90%, which is much higher than the 65% of the DEC-based electrolyte.

[0043] Figure 2 The charge and discharge curves of the LFP / / Li button cell with a PPS solid separator using the DMC-based electrolyte of Example 1 at -10°C and -20°C, and the capacity retention rate can reach 90% and 75% at room temperature.

[0044] Table 1 shows the coagulation test and electrochemical performance evaluation results of Examples 1 to 4 and Comparative Examples 1 to 2. From the coagulation test in Table 1, it can be seen that cosolvents such as ethyl propionate (EP), methyl propionate (MP), methyl acetate (MA), ethyl propionate (EP), and ethyl acetate (EA) can reduce the coagulation point of the electrolyte and make up for the defect of the high coagulation point of the DMC-based electrolyte.

[0045] From the electrochemical tests in Table 1, it can be seen that the combination of DMC-based electrolyte and PPS solid-state separator has better performance than the combination with commercial PE separator, both in the test of low-temperature capacity retention and in the test of high rate at room temperature, and has a slightly lower EMC than the freezing point (-53°C). This is due to the fact that this type of acyclic carbonate can form solvation clusters with lithium ions, which is easy to desolvate and decouple on the PPS surface, making it difficult for the solvent to block the transmission channel of the dense PPS separator, making Li + It can smoothly enter the sulfur channel on the surface of PPS at low temperature and migrate to the anode. In addition, the addition of linear ester cosolvents does not affect the rate performance of the battery at room temperature, and can make up for the high freezing point of the electrolyte and ensure the capacity retention rate at low temperature. However, DEC-based electrolytes are easily compatible with the surface of PPS, are not easily desolvated, and are easy to block the transmission interface of the dense diaphragm, thereby showing poor rate performance and low-temperature capacity retention rate.

[0046] Table 1 Coagulation test and electrochemical performance evaluation results of Examples 1 to 4 and Comparative Examples 1 to 2

[0047]

[0048] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0049] The embodiments are preferred implementations of the present invention, but the present invention is not limited to the above-mentioned implementations. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essential content of the present invention belong to the protection scope of the present invention.

Claims

1. A high-rate low-temperature-resistant electrolyte suitable for a high-density polyphenylene sulfide solid diaphragm, characterized in that: The invention comprises lithium salt, organic solvent and film-forming additive, wherein the organic solvent comprises acyclic carbonate solvent, cyclic carbonate solvent and cosolvent, the acyclic carbonate solvent is selected from acyclic carbonate which can produce weak dipole adsorption or repulsion with the surface of high crystalline polyphenylene sulfide PPS, and the adsorption energy barrier of the acyclic carbonate on the surface of PPS is greater than -0.33 eV; the cosolvent is a linear ester with a freezing point below -40°C.

2. The electrolyte according to claim 1, characterized in that In the lithium ion battery electrolyte, by mass percentage, the lithium salt accounts for 12%-18%; the film-forming additive accounts for 3%-5%; and the balance is an organic solvent, which is 100% in total.

3. The electrolyte according to claim 1, characterized in that In the organic solvent, the mass percentage of the cyclic carbonate solvent is 20%-30%, the mass percentage of the acyclic carbonate solvent is 40%-60%, and the mass percentage of the co-solvent is 20%-30%.

4. The electrolyte according to claim 1, characterized in that The cyclic carbonate solvent is selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), and vinylene carbonate (VC).

5. The electrolyte according to claim 1, characterized in that The acyclic carbonate solvent is selected from one or more of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), ethyl trifluoroethyl carbonate (ETFEC), and methyl trifluoroethyl carbonate (FEMC).

6. The electrolyte according to claim 1, characterized in that The co-solvent is selected from one or more of ethyl propionate (EP), methyl propionate (MP), methyl acetate (MA), ethyl propionate (EP), and ethyl acetate (EA).

7. The electrolyte according to claim 1, characterized in that The lithium salt is lithium hexafluorophosphate (LiPF6) and / or lithium bis(fluorosulfonyl)imide (LiFSI); the concentration of the lithium salt is 1.3-2 mol / L, and the mass percentage in the electrolyte is 12%-18%.

8. The electrolyte according to claim 1, characterized in that The film-forming additive is selected from one or more of lithium tetrafluoroborate (LiBF4), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), and tris(hexafluoroisopropyl) phosphate (THFP); the mass percentage of the film-forming additive in the electrolyte is 3%-5%.

9. The method for preparing an electrolyte according to any one of claims 1 to 8, characterized in that: According to the target composition and ratio of the electrolyte, lithium salt, acyclic carbonate, cyclic carbonate, linear ester and film-forming additive are weighed, and the acyclic carbonate, cyclic carbonate and linear ester are evenly mixed in a glove box filled with inert gas. Then, lithium salt and film-forming additive are added to the mixed solution, and the mixture is stirred to dissolve and evenly mixed to obtain the electrolyte.

10. A lithium battery, characterized in that: The electrolyte of the lithium battery is the electrolyte described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • A high-safety, high-volume energy-density quasi-solid-state lithium-ion battery and its manufacturing method

    CN111864272B

  • Lithium-ion secondary battery and electrolyte thereof

    CN103078141A

  • Separator and lithium secondary battery comprising same

    CN111247664A

  • Nonaqueous electrolyte for secondary battery, and nonaqueous electrolyte secondary battery

    CN115004436A

  • Full-tab large cylindrical iron lithium battery electrolyte and full-tab large cylindrical iron lithium battery

    CN117936903A

Cited By

  • Graded regulation and control electrolyte for improving low-temperature performance of lithium iron phosphate-based lithium ion battery and preparation method of graded regulation and control electrolyte

    CN121964835A